2007
DOI: 10.1111/j.1349-7006.2007.00601.x
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear translocation of ADAM‐10 contributes to the pathogenesis and progression of human prostate cancer

Abstract: A disintegrin and metalloproteases (ADAM) are cell membraneanchored proteins with potential implications for the metastasis of human cancer cells via cell adhesion and protease activities. In prostate cancer (PC), the ADAM-10 protein showed a nuclear localization whereas in benign prostate hypertrophy (BPH) it was predominantly bound to the cell membrane. We hypothesized that the pathogenesis and progression of PC are attributable to the nuclear translocation of ADAM-10. Immunoblotting revealed that after 5α α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
51
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 32 publications
2
51
0
Order By: Relevance
“…Both Cajal bodies and PML bodies are associated with actively transcribed gene loci involved in cell survival control (61,62), providing further circumstantial evidence for a nuclear function of ADAM10. Recently, translocation and colocalization of an ϳ60-kDa enzymatically active form of ADAM10 with the androgen receptor in the nuclear fraction of a prostate cancer was observed (68), opening the debate as to how these observations are interrelated with our observations of the 4-kDa ADAM10 nuclear fragment.…”
Section: Discussionmentioning
confidence: 74%
“…Both Cajal bodies and PML bodies are associated with actively transcribed gene loci involved in cell survival control (61,62), providing further circumstantial evidence for a nuclear function of ADAM10. Recently, translocation and colocalization of an ϳ60-kDa enzymatically active form of ADAM10 with the androgen receptor in the nuclear fraction of a prostate cancer was observed (68), opening the debate as to how these observations are interrelated with our observations of the 4-kDa ADAM10 nuclear fragment.…”
Section: Discussionmentioning
confidence: 74%
“…Ko et al (17) demonstrated that the expression of ADAM10 was correlated with increased growth of oral squamous cell carcinoma cells. Arima et al (27) confirmed that suppression of ADAM10 expression leads to a significant decrease in prostate cancer cell growth. The effect of ADAM10 on tumor cell growth may be related to its protease activity.…”
Section: Discussionmentioning
confidence: 95%
“…2A, panels 2 and 3). Based on published reports (29,30), the proenzyme form of ADAM10 migrates at ϳ100 kDa on a SDS-PAGE gel and the metabolically active form at ϳ60 kDa. Treatment with batimastat showed an increase in the levels of an ϳ80 kDa form of ADAM10, which was associated with a decrease in sAPP␣ generation (Fig.…”
Section: Pancreatic Cancer Cells Express High Levels Of App Andmentioning
confidence: 99%